Bangladesh : Education Sector Review, Volume 2 - World Bank (Dhaka: The University Press Limited for the World Bank, 2013)
This Education Sector Review covers many major educational topics in Bangladesh. Six actions are needed to realize Bangladesh's vision in 2020: build a stronger, wider and deeper foundation of basic education; reorient and establish secondary education on a more equitable footing; transfer vocational skill training to non-government providers; rationalize, reform and revitalize higher education; vastly increase public financing of education; and manage the system better. Volume 1: addresses the above six actions as well as socioeconomic development, implications for education, and education finance. Volume 2 examines in depth primary and pre-primary education; early childhood care and education for development; non-formal education; secondary; and higher secondary education. Volume 3: focuses on technical vocational education and training; and higher education.